Peradaban Islam: Hegemoni dan Kontribusinya di Bidang Sastra Arab - Abdul Latif (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2018)
Islamic Civilization is one of civilizations which has a prominent role in the world civilizations history. But many bad stereotypes has been given by Orientalist about Islamic Civilization. More than it, some of them also regard that Islamic Civilization has the lowest contribution in human civilization advancement. To know how Islamic Civilization ruled and had a role in developing civilization in that time, so the writer uses hegemony theory of Antonio Gramsci. The result of this research proves that there are two ways done by Islamic Civilization in ruling the society under its authority, first is by structured leadership led by the highest commander in Islam society civilization, and second is by morality leadership which that moral is taken from Alquran principals and values. Despite opinions above, Islamic Civilization contributions also has been acknowledged by European especially in this three sectors, it is in science, morality and thought. The contribution of Islamic civilization in the field of Arabic Literature is the presence of themes of heroism and the spirit of struggle in European literary works.